Moxibustion alleviates depression-like behavior in rats with Crohn’s disease by inhibiting the kynurenine pathway metabolism in the gut-brain axis - Bao, Chunhui; Huang, Jin; Wu, Huangan; Ma, Yueying; Zhou, Hongyu; Chen, Liming; Yang, Dandan; Liu, Huirong; Shi, Yin; Lu, Yuan (Frontiers in Neuroscience, 2022)
Background Moxibustion is a potential therapy for inflammatory bowel disease-related depression, but its specific mechanism of action is unclear. This study aimed to investigate the molecular mechanism by which moxibustion alleviates depressive behavior in rats with Crohn’s disease (CD). Methods The CD rat model was established with 2,4,6-trinitrobenzenesulfonic acid. Treatment with moxibustion was applied to Tianshu (ST25, bilateral), Qihai (CV6), and Baihui (GV20) acupoints, and the effect of moxibustion was compared with that of the combination of moxibustion plus indoleamine-2,3-dioxygenase 1 (IDO1) inhibitor, 1-methyltryptophan (1-MT). The effects of moxibustion and moxibustion plus 1-MT combination on colonic inflammation and depressive behavior (assessed by forced swimming test, sucrose preference test, and open field test) were investigated. The changes in IDO1, TNF-α, and IL-1β in rat colon and hippocampus were assessed by Western blot (WB). Gas chromatography-mass spectrometry, immunofluorescence staining, and WB were applied to detect kynurenine pathway (KP) metabolites, hippocampal neuronal activity, and microglia activation, respectively. Results Both moxibustion and moxibustion plus 1-MT combination significantly alleviated intestinal inflammation and depressive behavior, downregulated the levels of IDO1 in the colon and hippocampus, and inhibited inflammation-inducing factors IL-1β and TNF-α, as well as the kynurenine/tryptophan (KYN/TRP) ratio of KP metabolites, and upregulated the kynurenic acid (KYNA)/KYN ratio and the KYNA/quinolinic acid (QUIN) ratio in the hippocampus in rats with CD; Hippocampal ionized calcium-binding adaptor molecule-1 (Iba-1), c-fos protein expression, activated microglia, and neuronal activation was also significantly reduced by moxibustion and moxibustion plus 1-MT. The addition of 1-MT did not significantly increase the therapeutic effect of moxibustion. Conclusion Moxibustion can improve depressive behavior in rats with CD, which may be related to its regulation of KP metabolism in the gut-brain axis and inhibition of hippocampal microglia activation and neuronal activation.